Method for preparing high-coercivity sintered neodymium-iron-boron magnet
By attaching Pr-Dy-Cu-Ga quadrimer alloy sheets to the surface of the sintered NdFeB magnet substrate for grain boundary diffusion treatment, the problem of low utilization of rare earth resources in the traditional NdFeB magnet preparation method is solved, and the effect of performance optimization and cost reduction is achieved.
Patent Information
- Application Number
- CN202411654261.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-02-25
AI Technical Summary
In the prior art, the traditional NdFeB magnet preparation method has a low utilization rate of rare earth resources, resulting in the consumption of a large number of heavy rare earth elements and the increase in production costs.
Sintered NdFeB magnets are used as substrates, and Pr-Dy-Cu-Ga quad-alloy sheets are attached to their surfaces. The magnet performance is optimized through grain boundary diffusion treatment and the use of heavy rare earth elements is reduced.
Through this method, the coercive force and thermal stability of the neodymium iron boron magnet can be significantly improved, the use of heavy rare earth elements can be reduced, the production cost can be reduced, and the requirements of green and environmental protection can be met.
Smart Images

Figure CN119517594A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of rare earth permanent magnet material preparation, and more specifically, particularly relates to a method for preparing a high coercive force sintered NdFeB magnet. Background Art
[0002] Sintered NdFeB permanent magnet materials have been successfully used in various energy-efficient, small, reliable and multifunctional permanent magnet devices due to their excellent hard magnetic properties, constant magnetic field and efficient energy conversion functions. In the future, the ever-changing new energy and new equipment will put forward higher demands on the functions of sintered NdFeB magnets.
[0003] Sintered NdFeB is a multiphase crystal structure, the main phase is Nd2Fe 14 The strong interatomic exchange interaction and lattice anisotropy in B provide the magnet with intrinsic strong magnetism. The grain boundary phase, as a low-melting-point non-magnetic phase, is distributed at the grain boundaries and triangular intersections of the main phase, which can effectively isolate the magnetic exchange coupling between the grains of the main phase. This unique network grain boundary distribution will also cause the magnet to have poor thermal stability, shorten its life and deteriorate its performance in a high-temperature working environment. Heavy rare earths Dy and Tb are usually added to NdFeB magnets to improve the coercive force and thermal stability of the magnet. In recent years, due to the increasing demand for high-performance NdFeB magnets and the shortage of heavy rare earth Dy and Tb resources, the prices of heavy rare earths Dy and Tb have risen sharply, so how to reduce the amount of heavy rare earths Dy and Tb in the preparation of high-performance NdFeB magnets has become a hot topic of extensive research.
[0004] Grain boundary addition is widely used to improve the grain boundary structure of sintered magnets, and simultaneously improve the remanence and coercive force. The process is simple and has attracted widespread attention. This method is not limited by the shape and size of the magnet, and avoids the complex process of expansion heat treatment and repeated machining, which can significantly reduce the production cost investment. For example, the Chinese invention patent with patent number 201910899426.8 provides a method of using heavy rare earth compounds and high melting point metals as grain boundary phases to introduce and regulate the grain boundary structure combined with spark plasma sintering technology, shortening the preparation process to achieve the improvement of the magnetic properties of sintered NdFeB magnets. However, the use of this method to prepare NdFeB magnets will consume a large amount of heavy rare earths, and the current situation is that heavy rare earth element resources are becoming increasingly scarce. Another example is the Chinese invention patent with patent number 202311506703.7, which provides a method for preparing high-performance NdFeB magnets by combining the recycling of ultrafine powders, in-situ reduction reaction, addition of low-melting-point alloys and grain boundary diffusion technology in the preparation process of NdFeB magnets by jet milling. The mixed grain boundary diffusion powder is mixed with acetone solution to make it have good adhesion, but it is difficult to maintain the established multi-element alloy characteristics of the diffused material during the adhesion process, which greatly reduces the diffusion effect. In addition, the process of crushing the multi-element alloy ingot into powder or preparing the coating slurry is cumbersome and complicated, and the consistency of batch diffusion products is poor. In addition, due to the finer particle size requirements of rare earth alloy powders, it is easier to cause oxidation of alloy components, destroy the low melting point of multi-element alloy diffused materials, waste rare earth elements and deteriorate the diffusion effect. In view of this, it is very important to develop a method for manufacturing NdFeB magnet materials that can improve the performance of NdFeB and save costs. Summary of the invention
[0005] In order to solve the above technical problems, the present invention provides a method for preparing high coercive force sintered NdFeB magnets to solve the technical problem in the prior art that the traditional NdFeB magnet preparation method has low rare earth resource utilization rate, consumes a large amount of heavy rare earth, and increases production costs.
[0006] The purpose and effect of the method for preparing a high coercive force sintered NdFeB magnet of the present invention are achieved by the following specific technical means:
[0007] A method for preparing a high coercive force sintered NdFeB magnet comprises the following steps:
[0008] Step 1: Take the composition as (Pr, Nd) x Fe 100-x-y-z M y B z A sintered NdFeB magnet is used as a substrate, wherein M is at least one of Cu, Al, Ga, Mg, La, Ce, Dy, Zr, Gd, and Co, the substrate is processed into a block, and the surface of the sample is cleaned by alkaline washing to remove oil, ultrasonic water washing, and acid washing to remove the oxide layer;
[0009] Step 2: Mix the four diffusion source raw materials of Pr-Dy-Cu-Ga in proportion and melt them in a vacuum arc melting furnace for multiple times to obtain an alloy ingot with good uniformity as a diffusion source, cut the diffusion source alloy into thin slices and slightly grind the surface, then pickle and ultrasonically clean to remove the surface oxide layer;
[0010] Step 3: attach the thin slice to the surface of the substrate for heat treatment, diffuse at a temperature of 750-900°C for 4-6 hours, and use argon protection during the process;
[0011] Step 4: Temper the heat-treated magnet again at a temperature of 470-550°C for 2-3 hours, using argon protection during the process;
[0012] Step 5: Obtain a NdFeB magnet sample and measure its room temperature demagnetization curve.
[0013] In a preferred embodiment, in step one, the total weight proportion of Pr, Nd, Fe, M and B is 100 parts, wherein the sum of Pr and Nd is x parts, M is y parts, and B is z parts, which are: x is 28-32 parts, y is 0-2 parts, z is 0.8-1.2 parts, and Fe is 100-xyz parts.
[0014] In a preferred embodiment, the substrate is processed into a square with a length of 10 mm, a width of 10 mm and a height of 5 mm, and the height, that is, the thickness direction, is the magnetic field orientation direction.
[0015] In a preferred embodiment, the components of the solution required for alkali washing to remove oil are: 40-60 g / L sodium hydroxide, 50-70 g / L sodium carbonate, 30-40 g / L sodium phosphate and 25-40 g / L sodium silicate, the temperature is 70-80°C, and the time is 3-5 minutes.
[0016] In a preferred embodiment, the ultrasonic treatment time is 30 to 60 minutes, the frequency is 20 to 80 kHz, and the ultrasonic temperature is 50 to 80°C.
[0017] In a preferred embodiment, the solution required for pickling is 40-50 mL / L nitric acid and 0.3-0.6 g / L thiourea, and the time is 30 s.
[0018] In a preferred embodiment, in step 2, the Pr-Dy-Cu-Ga mixing ratio is as follows: 1 part of Pr, 0.5 to 4 parts of Dy, 0.003 to 0.02 parts of Cu and 0.003 to 0.02 parts of Ga by weight.
[0019] In a preferred embodiment, in step 2, the Pr-Dy-Cu-Ga mixing ratio is as follows: 1 part of Pr, 0.4-4 parts of Dy, 0.002-0.001 parts of Cu and 0.002-0.001 parts of Ga by weight.
[0020] In a preferred embodiment, in step 2, the Pr-Dy-Cu-Ga mixing ratio is as follows: 1 part of Pr, 0.3 to 3 parts of Dy, 0.0021 to 0.0095 parts of Cu and 0.0021 to 0.0095 parts of Ga by weight.
[0021] In a preferred embodiment, the diffusion source alloy is cut into thin slices with a length of 8 mm, a width of 8 mm, and a thickness of 200 μm.
[0022] The present invention uses sintered NdFeB magnet as a substrate and attaches alloy thin sheets thereon, optimizes magnet performance through grain boundary diffusion treatment, and avoids adding a large amount of heavy rare earth elements during the preparation of the substrate. Designing a quaternary alloy diffusion source instead of directly using Tb and Dy is also based on the direction of reducing the amount of heavy rare earth and controlling material costs. In the present invention, the Pr-Dy-Cu-Ga quaternary alloy diffusion source prepared by replacing the heavy rare earth element Dy with part of the light rare earth element Pr not only reduces the use of Dy but also optimizes the magnet performance after grain boundary diffusion. The addition of more low-melting-point Pr elements can well modify the microstructure of the magnet, reduce defects at the grain boundaries, make the Nd-rich phase more evenly distributed, form a continuous thin strip around the main phase grains, better inhibit the direct contact of the main phase grains, make the main phase grains smaller in size and increase in number, make the grain boundaries clear and smooth, and form a eutectic (Nd, Pr, Dy)2Fe 14 B shell layer, enhances the anisotropic field of the grain boundary. In addition, the low melting point elements Cu and Ga in the present invention can greatly improve the fluidity of the rare earth-rich phase during grain boundary diffusion heat treatment, which is conducive to the diffusion of heavy rare earth elements in the diffusion source to a deeper part of the NdFeB substrate. The present invention aims to obtain a sintered Nd-Fe-B magnet with excellent performance on the basis of optimizing the utilization rate of rare earth resources and reducing production costs, thereby meeting the requirements of green environmental protection.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] 1. Sintered NdFeB magnets are used as substrates, and alloy sheets are attached to them for grain boundary diffusion treatment to optimize magnet performance. In this process, a large amount of heavy rare earth elements are avoided from being added in the early stage of substrate preparation. In particular, a Pr-Dy-Cu-Ga quaternary alloy diffusion source is used to replace the heavy rare earth element Dy with part of the light rare earth element Pr, thereby reducing the amount of Dy used and making the magnet performance better after grain boundary diffusion. The magnet microstructure can be better modified, the defects at the grain boundaries can be reduced, the Nd-rich phase can be more evenly distributed, and a continuous thin strip can be formed around the main phase grains, which inhibits direct contact between the main phase grains, reduces the size of the main phase grains and increases the number of grains, and makes the grain boundaries clear and smooth, and eutectics form (Nd, Pr, Dy)2Fe 14 The B shell layer enhances the anisotropy field at the grain boundary, thereby improving the magnet performance while reducing the amount of heavy rare earth elements.
[0025] 2. By using quaternary alloy diffusion sources instead of directly using Tb and Dy, the amount of heavy rare earths used is reduced and the material cost is reduced; at the same time, the low melting point elements Cu and Ga can improve the fluidity of the rare earth-rich phase during grain boundary diffusion heat treatment, which is beneficial for the heavy rare earth elements in the diffusion source to diffuse deeper into the NdFeB substrate, further improving the resource utilization efficiency, and meeting the requirements of green environmental protection while obtaining sintered Nd-Fe-B magnets with excellent performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 The present invention is a flow chart of the steps of a method for preparing a high coercive force sintered NdFeB magnet.
[0027] Figure 2 It is a comparison diagram of the demagnetization curves of Example 1 and the original sample in a method for preparing a high coercive force sintered NdFeB magnet of the present invention.
[0028] Figure 3 It is a comparison diagram of demagnetization curves of Examples 2, 3, and 4 in a method for preparing a high coercive force sintered NdFeB magnet of the present invention, a comparative example, and an original sample.
[0029] Figure 4 This is the microscopic morphology of the magnet in Example 4 of the method for preparing a high coercive force sintered NdFeB magnet of the present invention. DETAILED DESCRIPTION
[0030] In order to further understand the present invention, preferred embodiments of the present invention are described below in conjunction with the accompanying drawings and examples. However, it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the present invention.
[0031] In the present invention, the weight ratio of Pr, Dy, Cu and Ga is most preferably: 1: (0.3-3): (0.0021-0.0095): (0.0021-0.0095). In the embodiments of the present invention, the weight ratio is specifically 1:3:0.0086:0.0086, 1:1:0.0043:0.0043 or 1:0.33:0.00286:0.00286.
[0032] A sintered NdFeB magnet with a composition of 7.20wt% Pr, 23.14wt% Nd, 0.17wt% Dy, 0.52wt% Co, 0.07wt% Ga, 0.12wt% Cu, 0.94wt% B and the rest Fe was used as a substrate. The substrate was processed into a 10mm×10mm×5mm (length×width×height) square, marked as the original sample, and its room temperature demagnetization curve was measured.
[0033] Embodiment 1:
[0034] Please refer to Figures 1 to 4 As shown, the present invention provides a method for preparing a high coercive force sintered NdFeB magnet, comprising the following steps:
[0035] Step 1: Take the composition as (Pr, Nd) x Fe 100-x-y-z M y B z A sintered NdFeB magnet is used as a substrate, wherein M is at least one of Cu, Al, Ga, Mg, La, Ce, Dy, Zr, Gd, and Co, and the substrate is processed into a block, and the surface of the sample is cleaned by alkaline washing to remove oil, ultrasonic water washing, and acid washing to remove the oxide layer; the processed block is placed in a solution of 50 g / L sodium hydroxide, 60 g / L sodium carbonate, 26 g / L sodium phosphate, and 30 g / L sodium silicate for alkaline washing to remove oil, the conditions are a temperature of 70°C and a time of 4 min; then, it is subjected to ultrasonic treatment for 45 min, a frequency of 40 kHz, and an ultrasonic temperature of 60°C, and then placed in a solution of 46 mL / L nitric acid and 0.5 g / L thiourea for surface acid washing, the conditions are room temperature and a time of 30 s;
[0036] Step 2: Use Pr-Dy-Cu-Ga quaternary alloy as the diffusion source [(Pr 75 Dy 25 ) 70 Cu 15 Ga 15, Pr:Dy:Cu:Ga=1:0.33:0.00286:0.00286], after multiple smelting in a vacuum arc melting furnace, an alloy ingot with good uniformity is obtained as a diffusion source, the diffusion source alloy is cut into a sheet with a height of 8 mm and a width of 8 mm and a thickness of 200 μm, and its surface is slightly polished;
[0037] Step 3: attach the thin film to the surface of the substrate for diffusion heat treatment at a temperature of 750°C for 6 hours, using argon protection during the process;
[0038] Step 4: Temper the heat-treated magnet again at 480°C for 3 hours, using argon protection during the process;
[0039] Step 5: Use NIM-5000H rare earth permanent magnet material measuring instrument to test the room temperature demagnetization curve of the sample and obtain the remanence B r , coercive force H cj and maximum magnetic energy product (BH) max Isomagnetic parameters, see Table 1 for specific parameters.
[0040] Embodiment 2:
[0041] Based on the method for preparing a high coercive force sintered NdFeB magnet provided in Example 1 of the present application, Example 2 of the present application proposes a method for preparing a high coercive force sintered NdFeB magnet. This Example 2 is only a preferred method of Example 1, and the implementation of Example 2 will not affect the independent implementation of Example 1. Example 2 of the present invention will be further described below.
[0042] A method for preparing a high coercive force sintered NdFeB magnet comprises the following steps:
[0043] Step 1: Take the composition as (Pr, Nd) x Fe 100-x-y-z M y B z A sintered NdFeB magnet is used as a substrate, wherein M is at least one of Cu, Al, Ga, Mg, La, Ce, Dy, Zr, Gd, and Co, and the substrate is processed into a block, and the surface of the sample is cleaned by alkaline washing to remove oil, ultrasonic water washing, and acid washing to remove the oxide layer; the processed block is placed in a solution of 50 g / L sodium hydroxide, 60 g / L sodium carbonate, 26 g / L sodium phosphate, and 30 g / L sodium silicate for alkaline washing to remove oil, the conditions are a temperature of 70°C and a time of 4 min; then, the block is subjected to ultrasonic treatment for 45 min, a frequency of 40 kHz, and an ultrasonic temperature of 70°C, and then placed in a solution of 46 mL / L nitric acid and 0.5 g / L thiourea for surface acid washing, the conditions are room temperature and a time of 30 s;
[0044] Step 2: Use Pr-Dy-Cu-Ga quaternary alloy as the diffusion source [(Pr 25 Dy 75 ) 70 Cu 15 Ga 15 , Pr:Dy:Cu:Ga=1:3:0.0086:0.0086], after multiple smelting in a vacuum arc melting furnace, an alloy ingot with good uniformity is obtained as a diffusion source, the diffusion source alloy is cut into a sheet with a height of 8mm and a width of 8mm and a thickness of 200μm, and its surface is slightly polished;
[0045] Step 3: attach the thin film to the surface of the substrate for diffusion heat treatment at a temperature of 800°C for 6 hours, using argon protection during the process;
[0046] Step 4: Temper the magnet after heat treatment at 490℃ for 3h, using argon protection during the process;
[0047] Step 5: Use NIM-5000H rare earth permanent magnet material measuring instrument to test the room temperature demagnetization curve of the sample and obtain the remanence B r , coercive force H cj and maximum magnetic energy product (BH) max Isomagnetic parameters, see Table 2 for specific parameters.
[0048] Embodiment three:
[0049] Based on the method for preparing a high coercive force sintered NdFeB magnet provided in Example 1 of the present application, Example 3 of the present application proposes a method for preparing a high coercive force sintered NdFeB magnet. This Example 3 is only a preferred method of Example 1, and the implementation of Example 3 will not affect the independent implementation of Example 1. Example 3 of the present invention will be further described below.
[0050] A method for preparing a high coercive force sintered NdFeB magnet comprises the following steps:
[0051] Step 1: Take the composition as (Pr, Nd) x Fe 100-x-y-z M y B zA sintered NdFeB magnet is used as a substrate, wherein M is at least one of Cu, Al, Ga, Mg, La, Ce, Dy, Zr, Gd, and Co, and the substrate is processed into a block, and the surface of the sample is cleaned by alkaline washing to remove oil, ultrasonic water washing, and acid washing to remove the oxide layer; the processed block is placed in a solution of 50 g / L sodium hydroxide, 60 g / L sodium carbonate, 26 g / L sodium phosphate, and 30 g / L sodium silicate for alkaline washing to remove oil, the conditions are a temperature of 70°C and a time of 5 min; then, it is subjected to ultrasonic treatment for 40 min, a frequency of 40 kHz, and an ultrasonic temperature of 60°C, and then placed in a solution of 46 mL / L nitric acid and 0.5 g / L thiourea for surface acid washing, the conditions are room temperature and a time of 30 s;
[0052] Step 2: Use a Pr-Dy-Cu-Ga quaternary alloy with a weight ratio of Pr to Dy of 1 part as a diffusion source [(Pr 50 Dy 50 ) 70 Cu 15 Ga 15 , Pr:Dy:Cu:Ga=1:1:0.0043:0.0043], after multiple smelting in a vacuum arc melting furnace, an alloy ingot with good uniformity is obtained as a diffusion source, the diffusion source alloy is cut into a sheet with a height of 8mm and a width of 8mm and a thickness of 200μm, and its surface is slightly polished;
[0053] Step 3: attach the thin film to the surface of the substrate for diffusion heat treatment at a temperature of 800°C for 6 hours, using argon protection during the process;
[0054] Step 4: Temper the magnet after heat treatment at 490℃ for 3h, using argon protection during the process;
[0055] Step 5: Use NIM-5000H rare earth permanent magnet material measuring instrument to test the room temperature demagnetization curve of the sample and obtain the remanence B r , coercive force H cj and maximum magnetic energy product (BH) max Isomagnetic parameters, see Table 2 for specific parameters.
[0056] Embodiment 4:
[0057] Based on the method for preparing a high coercive force sintered NdFeB magnet provided in Example 1 of the present application, Example 4 of the present application proposes a method for preparing a high coercive force sintered NdFeB magnet. This Example 4 is only a preferred method of Example 1, and the implementation of Example 4 will not affect the independent implementation of Example 1. Example 4 of the present invention will be further described below.
[0058] A method for preparing a high coercive force sintered NdFeB magnet comprises the following steps:
[0059] Step 1: Take the composition as (Pr, Nd) x Fe 100-x-y-z M y B z A sintered NdFeB magnet is used as a substrate, wherein M is at least one of Cu, Al, Ga, Mg, La, Ce, Dy, Zr, Gd, and Co, and the substrate is processed into a block, and the surface of the sample is cleaned by alkaline washing to remove oil, ultrasonic water washing, and acid washing to remove the oxide layer; the processed block is placed in a solution of 50 g / L sodium hydroxide, 60 g / L sodium carbonate, 26 g / L sodium phosphate, and 30 g / L sodium silicate for alkaline washing to remove oil, the conditions are a temperature of 70°C and a time of 4 min; then, the block is subjected to ultrasonic treatment for 45 min, a frequency of 40 kHz, and an ultrasonic temperature of 55°C, and then placed in a solution of 46 mL / L nitric acid and 0.5 g / L thiourea for surface acid washing, the conditions are room temperature and a time of 30 s;
[0060] Step 2: Use Pr-Dy-Cu-Ga quaternary alloy as the diffusion source [(Pr 75 Dy 25 ) 70 Cu 15 Ga 15 , Pr:Dy:Cu:Ga=1:0.33:0.00286:0.00286], after multiple smelting in a vacuum arc melting furnace, an alloy ingot with good uniformity is obtained as a diffusion source, the diffusion source alloy is cut into a sheet with a height of 8 mm and a width of 8 mm and a thickness of 200 μm, and its surface is slightly polished;
[0061] Step 3: attach the thin film to the surface of the substrate for diffusion heat treatment at a temperature of 800°C for 6 hours, using argon protection during the process;
[0062] Step 4: Temper the magnet after heat treatment at 490℃ for 3h, using argon protection during the process;
[0063] Step 5: Use NIM-5000H rare earth permanent magnet material measuring instrument to test the room temperature demagnetization curve of the sample and obtain the remanence B r , coercive force H cj and maximum magnetic energy product (BH) max Isomagnetic parameters, see Table 2 for specific parameters.
[0064] Comparative Example:
[0065] The comparative example of the present application proposes a method for preparing a high coercive force sintered NdFeB magnet. Through the comparative example, the embodiment of the present application is superior to the comparative example. The comparative example of the present invention will be further described below.
[0066] A method for preparing a high coercive force sintered NdFeB magnet comprises the following steps:
[0067] Step 1: Use Dy powder with a particle size of 30-50 μm to make a slurry; the slurry includes 50-80wt.% of Dy powder, 1.5-5wt.% of organic resin binder, and the rest is solvent, and stir it at a speed of 400-500r / min for 80-100min to obtain the desired coating slurry;
[0068] Step 2: Apply the prepared slurry on the surface of the original sample for high-temperature diffusion at a temperature of 800°C for 6 hours;
[0069] Step 3: Temper the heat-treated sample again at 490°C for 3h;
[0070] Step 4: Use NIM-5000H rare earth permanent magnet material measuring instrument to test the room temperature demagnetization curve of the sample and obtain the remanence B r , coercive force H cj and maximum magnetic energy product (BH) max Isomagnetic parameters, see Table 2 for specific parameters.
[0071] Table 1 (high temperature diffusion 750℃×6h; low temperature tempering 480℃×3h)
[0072]
[0073] Table 2 (high temperature diffusion 800℃×6h; low temperature tempering 490℃×3h)
[0074]
[0075] From the above, we can know that low melting point Cu and Ga can open diffusion channels, Dy has the effect of enhancing the anisotropy of the magnet. When the atomic ratio of Pr and Dy is 3:1, a large amount of Pr replaces Dy into the main phase and increases the amount of rare earth in the main phase grains. The addition of Pr elements will further improve the microstructure of the magnet, increase the wettability of the grain boundary phase, and reduce the irregular edges and corners of the main phase grains. Microstructure modification is the main reason for the significant increase in coercive force. When only Dy is used for diffusion, the results are not as good as those of alloy diffusion in terms of performance improvement and economy. Overall, grain boundary diffusion (Pr 75 Dy 25 ) 70 Cu 15 Ga 15The alloy magnet has better comprehensive performance, reduces the amount of heavy rare earth used, greatly saves preparation costs, and the equipment used is conventional equipment, which can meet and realize mass production and promotion.
[0076] The embodiments described above are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. Such modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention, and should all be included in the protection scope of the present invention.
Claims
1. A method for preparing a high coercive force sintered NdFeB magnet, characterized in that: The following steps are included: Step 1: Take the composition as (Pr, Nd) x Fe 100-x-y-z M y B z A sintered NdFeB magnet is used as a substrate, wherein M is at least one of Cu, Al, Ga, Mg, La, Ce, Dy, Zr, Gd, and Co, the substrate is processed into a block, and the surface of the sample is cleaned by alkaline washing to remove oil, ultrasonic water washing, and acid washing to remove the oxide layer; Step 2: Mix the four diffusion source raw materials of Pr-Dy-Cu-Ga in proportion and melt them in a vacuum arc melting furnace for multiple times to obtain an alloy ingot with good uniformity as a diffusion source, cut the diffusion source alloy into thin slices and slightly grind the surface, then pickle and ultrasonically clean to remove the surface oxide layer; Step 3: attach the thin slice to the surface of the substrate for heat treatment, diffuse at a temperature of 750-900°C for 4-6 hours, and use argon protection during the process; Step 4: Temper the heat-treated magnet again at a temperature of 470-550°C for 2-3 hours, using argon protection during the process; Step 5: Obtain a NdFeB magnet sample and measure its room temperature demagnetization curve.
2. The method for preparing a high coercive force sintered NdFeB magnet according to claim 1, characterized in that: In step 1, the total weight of Pr, Nd, Fe, M and B is 100 parts, wherein the sum of Pr and Nd is x parts, M is y parts, and B is z parts, which are: x is 28-32 parts, y is 0-2 parts, z is 0.8-1.2 parts, and Fe is 100-xyz parts.
3. The method for preparing a high coercive force sintered NdFeB magnet according to claim 1, characterized in that: The substrate is processed into a square block with a length of 10 mm, a width of 10 mm and a height of 5 mm, and the height, that is, the thickness direction, is the magnetic field orientation direction.
4. The method for preparing a high coercive force sintered NdFeB magnet according to claim 1, characterized in that: The solution components required for the alkaline washing to remove oil are: 40-60g / L sodium hydroxide, 50-70g / L sodium carbonate, 30-40g / L sodium phosphate and 25-40g / L sodium silicate, the temperature is 70-80°C, and the time is 3-5min.
5. The method for preparing a high coercive force sintered NdFeB magnet according to claim 1, characterized in that: The ultrasonic treatment time is 30 to 60 minutes, the frequency is 20 to 80 kHz, and the ultrasonic temperature is 50 to 80°C.
6. The method for preparing a high coercive force sintered NdFeB magnet according to claim 1, characterized in that: The solution required for the pickling is 40-50 mL / L of nitric acid and 0.3-0.6 g / L of thiourea, and the pickling time is 30 s.
7. The method for preparing a high coercive force sintered NdFeB magnet according to claim 1, characterized in that: In step 2, the Pr-Dy-Cu-Ga mixing ratio is as follows: 1 part of Pr, 0.5-4 parts of Dy, 0.003-0.02 parts of Cu and 0.003-0.02 parts of Ga by weight.
8. The method for preparing a high coercive force sintered NdFeB magnet according to claim 1, characterized in that: In step 2, the Pr-Dy-Cu-Ga mixing ratio is as follows: 1 part of Pr, 0.4-4 parts of Dy, 0.002-0.001 parts of Cu and 0.002-0.001 parts of Ga by weight.
9. The method for preparing a high coercive force sintered NdFeB magnet according to claim 1, characterized in that: In step 2, the Pr-Dy-Cu-Ga mixing ratio is as follows: 1 part of Pr, 0.3 to 3 parts of Dy, 0.0021 to 0.0095 parts of Cu and 0.0021 to 0.0095 parts of Ga by weight.
10. The method for preparing a high coercive force sintered NdFeB magnet according to claim 1, characterized in that: The diffusion source alloy was cut into a thin sheet with a length of 8 mm, a width of 8 mm, and a thickness of 200 μm.
Citation Information
Patent Citations
Method for preparing high-performance sintered neodymium-iron-boron magnet based on grain boundary addition
CN110534280A
Preparation method for efficient grain boundary diffusion of neodymium-iron-boron magnet
CN117275926A
Cited By
A method for preparing sintered NdFeB with high remanence and high coercivity
CN119742172A
High-temperature-resistant high-residual-magnetism rare earth permanent magnet material and preparation process thereof
CN120527108A
Preparation method for sintered neodymium iron boron having high remanence and high coercivity
WO2026183689A1